2012
DOI: 10.1108/00070701211213519
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the hedonic price for Fair Trade coffee in Sweden

Abstract: Purpose -This study aims to investigate the impact of the Fair Trade label on the market for coffee in Sweden, a country with high public awareness regarding environmental and social matters. Design/methodology/approach -A revealed preference approach is adopted, using weekly scanner sales panel data made available by Nielsen and the Swedish Retail Institute (HUI). The pricing of labelled coffee is studied over the 2005-2008 period. Hedonic estimates are obtained for what consumers pay for different product ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 32 publications
1
41
1
1
Order By: Relevance
“…In addition, while most of the studies on sustainable certified coffee focused only on Fair Trade (Cicia et al, 2010;de Ferran and Grunert, 2007;De Pelsmacker et al, 2005a;Hainmueller et al, 2015;Koppel and Schulze, 2013;Rotaris and Danielis, 2011;Schollenberg, 2012;Yang et al, 2012Yang et al, , 2013, or eco-friendly (Sörqvist et al, 2013), only a few have assessed the consumer trade-offs between Fair Trade and other sustainability labels such as Organic (Basu and Hicks, 2008;Cranfield et al, 2010;De Pelsmacker et al, 2005b;Langen, 2011), or shade grown coffee (Loureiro and Lotade, 2005). These studies found that Fair Trade coffee was generally preferred over Organic coffee by consumers in Belgium (De Pelsmacker et al, 2005b), Germany (Basu and Hicks, 2008) and the US (Basu and Hicks, 2008;Loureiro and Lotade, 2005).…”
Section: Sustainability Labels On Coffee: An Overviewmentioning
confidence: 94%
“…In addition, while most of the studies on sustainable certified coffee focused only on Fair Trade (Cicia et al, 2010;de Ferran and Grunert, 2007;De Pelsmacker et al, 2005a;Hainmueller et al, 2015;Koppel and Schulze, 2013;Rotaris and Danielis, 2011;Schollenberg, 2012;Yang et al, 2012Yang et al, , 2013, or eco-friendly (Sörqvist et al, 2013), only a few have assessed the consumer trade-offs between Fair Trade and other sustainability labels such as Organic (Basu and Hicks, 2008;Cranfield et al, 2010;De Pelsmacker et al, 2005b;Langen, 2011), or shade grown coffee (Loureiro and Lotade, 2005). These studies found that Fair Trade coffee was generally preferred over Organic coffee by consumers in Belgium (De Pelsmacker et al, 2005b), Germany (Basu and Hicks, 2008) and the US (Basu and Hicks, 2008;Loureiro and Lotade, 2005).…”
Section: Sustainability Labels On Coffee: An Overviewmentioning
confidence: 94%
“…In 1974, Rosen introduced HPM into the real estate industry and made it develop vigorously [6]. Schollenberg et al studied the house price change in Sweden based on HPM [7]. Andrewson et al found that there are spatial autocorrelations and spatial error variables in the sample data when analyzing the relationship between house price and spatial influencing factors.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have found the important quality attributes of apple any preliminary analysis [Carew (2000), Huang & Lin (2007), Carew et al (2012), Schollenberg (2012), Gurung, 2013)]. …”
Section: Figure 1 Consumers' Equilibrium Onmentioning
confidence: 99%